UTILIZING SOCIAL ROBOT TO REDUCE WORKLOAD OF HEALTHCARE PROFESSIONALS IN PSYCHIATRIC HOSPITAL: A PRELIMINARY STUDY. (11th November 2018) - Ikeuchi, T; Sakurai, R; Furuta, K; Kasahara, Y; Imamura, Y; Shinkai, S
Abstract: This study implemented an intervention program to examine the benefits and challenges of utilizing a humanoid social robot (Pepper) for healthcare professionals who work with patients with dementia in an acute hospital setting in Japan. Two 30-minute programs consisting of light physical and social activities (e.g., singing a song together) were installed on Pepper for the patients with dementia to enjoy while sitting in a chair. The program itself was run by the robot, but operated by researchers twice a week for two months. At each session, 10 to 15 patients participated. Healthcare professionals (68% nurses and 32% clinical psychologists) completed pre- (n=24) and post- (n=20) surveys. There were no statistical differences in the pre- and post-survey results. However, an additional question of whether any changes were noticed, which was included only in the post-survey, indicated decreased workloads (25% reported) and increased patients' smiles (45% reported). On the other hand, 25% reported increased behavior problems of the patients (e.g., agitation) that were observed particularly after these sessions. Although the cause of such behavior problems was unclear, we noted that most patients were very concentrated on Pepper during the sessions, which may have resulted in higher levels of stimulation of the patients. These results demonstrate potential benefits of utilizing a social robot in dementia care in hospital settings. However, a follow-up process may be necessary to undertake in the operation, such as including a short closing activity in order to unwind and ease the stimulation of the patients with dementia.